2010
DOI: 10.1126/science.1189072
|View full text |Cite
|
Sign up to set email alerts
|

Linear Arrays of Nuclear Envelope Proteins Harness Retrograde Actin Flow for Nuclear Movement

Abstract: Nuclei move to specific locations to polarize migrating and differentiating cells. Many nuclear movements are microtubule-dependent. However, nuclear movement to reorient the centrosome in migrating fibroblasts occurs through an unknown actin-dependent mechanism. Here, we found that linear arrays of outer (nesprin2G) and inner (SUN2) nuclear membrane proteins assembled on and moved with retrogradely moving dorsal actin cables during nuclear movement in polarizing fibroblasts. Inhibition of nesprin2G, SUN2 or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

33
565
5
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 417 publications
(605 citation statements)
references
References 26 publications
33
565
5
2
Order By: Relevance
“…In addition, given recent interests on molecular linkages between apical actin filaments and nuclear membrane 18,19 , it will be interesting to investigate whether such links exist for central actin filaments and influence the force transmission process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, given recent interests on molecular linkages between apical actin filaments and nuclear membrane 18,19 , it will be interesting to investigate whether such links exist for central actin filaments and influence the force transmission process.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Khatau et al 18 have reported the presence of a dome-like actin structure, called the actin cap, that covers the top of the nucleus, and their results suggest that this structure is involved in a part of the nuclear shape deformation. More recently, a physical connection between an array of actin filaments located above the nucleus and the nuclear membrane, called transmembrane actin-associated nuclear lines, have been observed to be implicated in the intracellular localization of the nucleus 19 . Furthermore, perturbations of the intermediate filament network could alter the positioning of the nucleus in both migrating and immobile astrocytes, suggesting that cytoplasmic intermediate filaments are involved in actin-dependent positioning of the nucleus 20 .…”
mentioning
confidence: 99%
“…In the lumen of the NE, the SUN domain interacts with the KASH domain, ensuring that KASH domain proteins are targeted to the ONM. During actin-dependent nuclear movement, the LINC complex components Nesprin 2G and SUN2 were found to provide a direct linkage between the nucleus and the actin network [18,19]. Recently, mutations of KASH domain proteins have been linked to Emery-Dreifuss muscular dystrophy [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Nesprins interact with cytoskeletal elements, and both nesprins and SUNs contribute to nuclear movement and positioning during development and in migrating cells (10)(11)(12)(13). Recent work has shown that multiple LINC complexes assemble into transmembrane actin-associated nuclear (TAN) lines that attach nuclei to actin filaments during nuclear movement as fibroblasts polarize to migrate (13).…”
mentioning
confidence: 99%
“…Interactions between the nucleus and cytoskeleton are mediated by the linker of nucleoskeleton and cytoskeleton (LINC) complex, which spans the nuclear envelope via nesprin proteins in the outer nuclear membrane and SUN proteins in the inner nuclear membrane (9). Nesprins interact with cytoskeletal elements, and both nesprins and SUNs contribute to nuclear movement and positioning during development and in migrating cells (10)(11)(12)(13). Recent work has shown that multiple LINC complexes assemble into transmembrane actin-associated nuclear (TAN) lines that attach nuclei to actin filaments during nuclear movement as fibroblasts polarize to migrate (13).…”
mentioning
confidence: 99%